Influence of immediate loading on healing of implants installed with different insertion torques - an experimental study in dogs - Rea, Massimiliano; Botticelli, Daniele [UNESP]; Ricci, Sara; Soldini, Claudio; Gonzalez Gonzalez, Gladys; Lang, Niklaus P. (Wiley-Blackwell, 2015)
Objective: To evaluate the influence of different insertion torques on healing of implants loaded immediately or left unloaded.Material and methods: In six Labrador dogs, all mandibular premolars and molars were extracted. After 4 months of healing, flaps were elevated, and two implant sites were prepared at each side of the mandible. The distal sites were prepared conventionally while the mesial sites were underprepared by 0.3 mm. As a consequence, different final insertion torques of about 30 Ncm at the distal and >70 Ncm at the mesial sites were recorded. Healing abutments were applied to the left and transmucosal abutments to the right side. Flaps were sutured, crown preparation of the upper right second and third premolars was performed, and impressions were taken. Within 24 h, crowns were cemented both to implants and teeth in the right side of the mouth. After 4 months, the animals were sacrificed and ground sections obtained for histological evaluation.Results: A higher buccal bony crestal resorption and a more apical position of the coronal level of osseointegration were found at the loaded compared with the unloaded sites. MBIC% and percentages of peri-implant mineralized tissue (MB%) were higher at the loaded compared with the unloaded sites. Moreover, a higher MBIC% was found at the lower compared with the higher final insertion torque.Conclusions: Immediate loading does not seem to have a negative effect on osseointegration. High torque values for the immediate loading procedures were not necessary. Probably, low torque values, were sufficient to obtain primary stability and hence may provide better osseointegration than high torque value.
Keywords: animal study; bone healing; dental implants; histology; immediate loading; implant dentistry; insertion torque; prosthesis